Measuring ocean literacy in pre-service teachers: psychometric properties of the Greek version of the Survey of Ocean Literacy and Experience (SOLE). Issue 2 (7th February 2017) - Markos, Angelos; Boubonari, Theodora; Mogias, Athanasios; Kevrekidis, Theodoros
Abstract : The aim of the present study was to respond to the increasing demand for comprehensive tools for the measurement of ocean literacy, by investigating the psychometric characteristics of a Greek version of the Survey of Ocean Literacy and Experience (SOLE), an instrument that assesses conceptual understanding of general ocean sciences content, focusing on the knowledge component. Four hundred twenty-one pre-service primary school teachers participated in a cross-sectional study. The dichotomous Rasch model was used to examine the measurement properties of the SOLE, namely, person-item targeting and separation, reliability, dimensionality and differential item functioning (DIF). Steps were taken to improve the instrument, where any of these attributes were outside acceptable ranges. Results suggested that a modified SOLE showed an adequate fit to the Rasch model, is unidimensional, free of DIF, and is particularly well-suited to the population under study. Our findings suggest that the SOLE constitutes a valuable tool which can be applied to a different cultural context and population. The proposed use of the instrument could contribute to the assessment of the quality of marine education in school-based and non-formal education contexts and to the cross-cultural comparison of ocean literacy, which are prerequisites for the improvement of ocean literacy.